Fighting talk: Organisational discourses of the conflict over raptors and grouse moor management in Scotland. (September 2018) - Hodgson, Isla D.; Redpath, Steve M.; Fischer, Anke; Young, Juliette
Highlights: We analysed the discourses of six high-profile organisations with conflicting interests. Organisations offered diverging interpretations of central issues. Discursive strategies were employed to gain 'dominance' in the debate. Discourses were dismissive of the motives and actions of other actors. Discursive contestation at this level could widen barriers between stakeholders and damage conflict mitigation efforts. Abstract: Conflict is currently one of the greatest challenges facing wildlife conservation. Whilst conflicts may first appear to concern wildlife, they are often embedded within wider debates surrounding land use, land ownership, and the governance of natural resources. Disputes over the impacts or management of a species therefore become symbols for conflicts that are fundamentally between the divergent interests and values of the people involved. NGOs representing the interests of local stakeholders can become actors within the conflict, often utilising publicly available platforms such as websites and social media in an attempt to influence over others and gain a dominant foothold in the debate. Here, we examined discourses of organisations in relation to a contentious and high-profile case of conflict in Scotland, that occurs between interests of raptor conservation and grouse moor management. News articles sourced from the websites of six organisations – identified as key voices in the debate – were subjected to discourse analysis. 36 storylines were drawn from common phrases and statements within the text. Storylines demonstrated a clear divide in the discourse; organisations differed not only in their portrayal of central issues, but also in their representation of other actors. Discourses were strategic; organisations interpreted the situation in ways that either supported their own interests and agendas, or damaged the image of opposing parties. We argue that discursive contestation at this level could be damaging to mitigation efforts – widening barriers between stakeholders and risking already fragile relationships. This in turn reduces the likelihood of consensus and impacts on successful decision-making and policy implementation. We conclude that conflict managers should be aware of the contestation between high-profile actors, and the ramifications this may have for conflict mitigation processes. An understanding of what constitutes these discourses should therefore be used as a foundation to improve dialogue and collaborative management.